HUBUNGAN ANTARA SELF EFICACY DENGAN KINERJA PERAWAT DALAM MELAKSANAKAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSUD dr. R. KOESMA TUBAN - Tiara Putri Ryandini; Mokhamad Nurhadi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Self-efficacy is a sense of confidence in oneself that individuals can face the problems that are being experienced and can provide positive results. Performance is the successful completion of a task or meeting a set target. This study aims to determine the relationship between Self Efficacy with the performance of nurses in carrying out nursing care in the hospital dr. R. Koesma Tuban. This type of research is correlational using a cross-sectional time approach with a population of 39 nurses selected by cluster random sampling technique of as many as 36 nurses. The independent variable is self-efficacy and the dependent is the performance of nurses in carrying out nursing care measured using the Spearmen correlation test. The results of the study were conducted after the analysis using the Spearmen correlation test with significance level ρ = ≤ 0.05. The results of the study on the relationship between self-efficacy with the performance of nurses in implementing nursing care proved that p = 0.000 indicates the value of ρ < ɑ (0.04 < 0.05) which means H1 is accepted that there is a relationship between Self Efficacy with the performance of nurses in implementing nursing care in inpatient hospital dr. R. Koesma Tuban, with a correlation value of 0.468, which is a strong correlation with a positive direction. from the description above it can be concluded that the relationship between Self Efficacy with the performance of nurses in carrying out nursing care in the inpatient hospital dr. R. Koesma Tuban . Keywords: Implementing Nursing Care, Nurse Performance, Self Efficacy